2001
DOI: 10.1046/j.0956-540x.2001.1484.484.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth distribution of earthquakes in the Baikal rift system and its implications for the rheology of the lithosphere

Abstract: Summary The correspondence between the predicted brittle–plastic transition within the crust and the maximum depth of earthquakes is examined in the case of the Baikal rift, Siberia. Although little accurate information on depths is available through large‐ and moderate‐size earthquakes, there are frequent indications of foci at 20 km depth and more. We have relocated 632 events recorded at nearby stations that occurred between 1971 and 1997, with depth and epicentral uncertainties less than 5 km, over the eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 79 publications
5
102
0
3
Order By: Relevance
“…[3] Many investigators have suggested that the development of the rift system has not been influenced to any great extent by warm upwelling mantle material beneath the rift because of the paucity of magmatism in the rift system, and the strength of the rifted lithosphere, as manifest in the gravity field [Diament and Kogan, 1990;Ruppel et al, 1993;Petit et al, 1997] and the prevalence of deep crustal earthquakes [Deverchere et al, 1991[Deverchere et al, , 1993[Deverchere et al, , 2001. Some seismic studies of upper mantle structure find little evidence for a significant thermal anomaly beneath the rift system and therefore support this view [e.g., ten Brink and Taylor, 2002], while others report slower-than-average upper mantle velocities beneath portions of the rift system, consistent with the presence of thermally modified lithosphere [e.g., Puzyrev et al, 1978;Logatchev and Zorin, 1992;Gao et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Many investigators have suggested that the development of the rift system has not been influenced to any great extent by warm upwelling mantle material beneath the rift because of the paucity of magmatism in the rift system, and the strength of the rifted lithosphere, as manifest in the gravity field [Diament and Kogan, 1990;Ruppel et al, 1993;Petit et al, 1997] and the prevalence of deep crustal earthquakes [Deverchere et al, 1991[Deverchere et al, , 1993[Deverchere et al, , 2001. Some seismic studies of upper mantle structure find little evidence for a significant thermal anomaly beneath the rift system and therefore support this view [e.g., ten Brink and Taylor, 2002], while others report slower-than-average upper mantle velocities beneath portions of the rift system, consistent with the presence of thermally modified lithosphere [e.g., Puzyrev et al, 1978;Logatchev and Zorin, 1992;Gao et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…The stress barrier is maintained only in the elastic layer. Observations of deep seismicity in young rifts suggest a strong midlower crust [17][18][19] that maintains the stresses necessary to create a stress barrier at any crustal depth. If the lower crust and upper mantle are weak, the elastic stresses dissipate and z 2 may coincide with the bottom of the elastic layer.…”
mentioning
confidence: 99%
“…практически до подошвы коры (например (Déverchère et al, 2001)]. Эти землетрясения могут свидетельствовать о пе-реходе к пластическому режиму деформаций на глубинах, превышающих 30 км, и о хрупкости коры на меньших глубинах.…”
Section: обсуждение результатовunclassified